Cytokine Profiling Associated with Bovine Tuberculosis - Kaur, Gurleen; Filia, Gursimran; Leishangthem, Geeta Devi; Mahajan, Vishal (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Cytokine expression in bovine tuberculous tissues was estimated and compared to that of non-infected healthy tissue samples using ELISA. Twenty tissue samples suspected of bovine tuberculosis were collected and subjected to a preliminary acid-fast staining technique followed by molecular detection using IS6110 PCR. The expression of anti-inflammatory cytokines interleukin IL-4 and IL-13, immunomodulator IL-10, and the pro-inflammatory cytokines tumour necrosis factor (TNF-α) and interferon-gamma (IFN-γ) were estimated in the tissue samples positive for bovine tuberculosis. The dominance of pro-inflammatory cytokines (IFN-γ and TNF-α) over the anti-inflammatory cytokines (IL-4 and IL-13) in the tuberculosis-infected tissues indicated that the pro-inflammatory cytokines played a crucial role in the tissue damage occurring in the disease. Immunomodulatory cytokine IL-10 levels were also significantly increased indicating its role in the maintenance of the balance of the cytokines. Thus, the present study revealed that cytokines play a major role in the immunopathogenesis of bTB.